Faktor Risiko Postpartum Depression dalam Konteks Geografis, Sosial, dan Ekonomi - Recavery Dwi Wulandari; Wening Pangesthi Maharani; Nevy Norma Renityas; Dyah Mubarokah Ahadiyati (Jurnal Medika Nusantara, 2025)
Postpartum Depression is also known as PPD, which is a maternal mental health condition that affects each woman worldwide significantly and also potentially influences mothers' and babies' conditions. Various socioeconomic, environmental, and geographic conditions determine the prevalence and the risk factors of PPD. This study aims to identify and analyze the primary factors associated with PPD. This systematic review utilizes articles from PubMed, Elsevier, Google Scholar, and other academic databases published between 2020 and 2025, particularly focusing on differences in PPD prevalence between rural and urban areas. Seven articles were selected based on the inclusion criteria. The results indicate that low educational attainment, prior mental disorders, lack of social support, limited access to health care services, low economic condition, and complications in pregnancy or childbirth significantly increase the risk of PPD. Therefore, advancing mental health services, promoting the involvement of partners and families, as well as mediating interventions related to socio-economics are fundamental strategies to mitigate the incidence of PPD.